PROGRAM SYNTHESIS INDICATOR MATRICES FOR SYSTEMS VILENKYN-KRESTENSONA FUNCTIONS - Білецький, А.; Дем’яник, Д. (Science-based technologies, 2010)
The article is dedicated to the researching of orthogonal basis of Vilenkin-Krestenson functions. Signal’s spectrumcan be obtained faster in this basis than in classic Fourier’s trigonometrical basis. The second it’s advantageis ability to synthesize in few degrees more symmetrical transform matrices than for classic basis. Thesynthesis of these matrices is the object of this article.